POLA RELASI SUAMI ISTRI TERHADAP KELANGGENGAN PERNIKAHAN DALAM KELUARGA MODERN - Nurwandayani; Rosmiati Daya; A Ratnawati; Saripuddin; Sarajuddin; Muhammad Nawir (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Marriage is a bond that aims to form a harmonious and sustainable family. Building a husband-wife relationship is a very crucial aspect in the sustainability of marriage. This study aims to examine the influence of husband-wife relationship patterns on the sustainability of marriage in modern families. The method used is a literature study by collecting and analyzing various library sources in the form of books, journal articles, and research results relevant to the research theme. The data obtained were analyzed descriptively qualitatively. The results of the study indicate that: Husband-wife relationship patterns include owner-property and head-complement relationship patterns, senior-partner and equal partner relationship patterns. Harmonious relationship patterns can be a strong foundation for creating a stable and emotionally supportive family. Conversely, unhealthy relationship patterns, such as minimal communication, a dominating attitude, or a lack of respect for one's partner, can trigger various problems that have the potential to disrupt household harmony. Furthermore, the rights and obligations of husband and wife include joint rights and the rights of children in Islam, namely the right to live and develop.